2014
DOI: 10.18552/aprj.v1i2.146
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Coping in IAPT Staff: a Mixed Methods Study

Abstract: Background: Research indicates National Health Service (NHS) mental health workers have particularly high levels of stress. Improving Access to Psychological Therapies (IAPT) is an NHS mental health service with new ways of working. Aims: This exploratory study sought to investigate whether IAPT staff experience high levels of stress and, moreover, identify sources of stress and ways of coping.Method: A mixed methods design was utilised. Forty four IAPT workers completed a quantitative survey in which prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Whilst there were no significant differences reported in terms of any of the variables of interest for those who dropped out before completing the measures a second time and those who did not, the over-representation of IAPT trainees amongst non-completers further indicates that caution must again be applied when interpreting these results for IAPT trainees. In contrast to the two studies discussed above, the studies of Walklet and Percy (2014) and Kostaki (2018) reported comparatively high levels of stress in IAPT professionals. Kostaki's (2018) study of 207 IAPT clinicians used the Perceived Stress Scale (Cohen and Williamson, 1988) to measure stress and reported that IAPT professionals experience higher levels of stress than normative data for the measure and are 'among the higher end' of scorers recorded for healthcare professionals (Kostaki, 2018).…”
Section: Levels Of Stress and Burnout In Iapt Trainees Stressmentioning
confidence: 68%
See 4 more Smart Citations
“…Whilst there were no significant differences reported in terms of any of the variables of interest for those who dropped out before completing the measures a second time and those who did not, the over-representation of IAPT trainees amongst non-completers further indicates that caution must again be applied when interpreting these results for IAPT trainees. In contrast to the two studies discussed above, the studies of Walklet and Percy (2014) and Kostaki (2018) reported comparatively high levels of stress in IAPT professionals. Kostaki's (2018) study of 207 IAPT clinicians used the Perceived Stress Scale (Cohen and Williamson, 1988) to measure stress and reported that IAPT professionals experience higher levels of stress than normative data for the measure and are 'among the higher end' of scorers recorded for healthcare professionals (Kostaki, 2018).…”
Section: Levels Of Stress and Burnout In Iapt Trainees Stressmentioning
confidence: 68%
“…The eight studies included in the review form a varied collection of research, employing quantitative, qualitative and mixed methods approaches. Only two of the studies are published in peer-reviewed journals (Walklet and Percy, 2014;Westwood et al, 2017); the remaining six are doctoral theses. Both the total number of participants and the proportion of those who were IAPT trainees varied significantly between studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations